A feature selection approach to determine obesity using machine learning method - Antor, Shahidul Alam; Ahmed, Jawad; Nayen, Zulker; Tabassum, Farisha; Mahbub, Rasheda (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.